Multi-Hamiltonian Structures on Beauville's Integrable System and Its Variant - Inoue, R.; Konishi, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We study Beauville's completely integrable system and its variant from a viewpoint of multi-Hamiltonian structures. We also relate our result to the previously known Poisson structures on the Mumford system and the even Mumford system.